Characteristics of Patients with Anterior Cruciate Ligament Injury at Ulin Hospital Banjarmasin, Indonesia - Damayanthi, Essy Dwi; Hosea, Nathania (Faculty of Medicine, Universitas Padjadjaran, 2025)
Knee injuries are one of the common injuries, especially among athletes. Many studies have concluded that the main cause of these injuries were sudden movements while doing sports. The incidence of the knee joint injury in Indonesia was 38 to 78 per 100,000 patients with the prevalence of Anterior Cruciate Ligament (ACL) injuries of 16%. Recently, an increasing number of ACL injury patients was observed to be treated at the Ulin Hospital, Banjarmasin, Indonesia, when compared to the number of the previous years, making it important to understand the characteristics of patients experiencing these injuries. This study aimed to explore the characteristics of patients with ACL injuries in the hospital. Data for this retrospective descriptive study were collected from medical records during the period of March 2022 to June 2023 from Ulin Hospital, Banjarmasin. The inclusion criteria were patients diagnosed with an ACL injury with or without meniscus tear. From a total of 95 patients with ACL injuries, 30 (32%) were below 20 years old, 42 (44%) were 20-30 years old, 18 (19%) were 31-40 years old, 3 (3%) were 41-50 years old, and 2 (2%) were above 50 years old. The ratio between men and women was 11:1. There were 74 patients who had sports-related injuries while the remaining 21 patients experienced the injury due to other activities. Of the total 95 cases, 59 (62%) were treated nonoperatively and 36 (38%) received arthroscopy surgery. The arthroscopy was mostly performed to patients who also experienced a meniscus injury and in the chronic phase, with an average length of stay at the hospital of 2.6 days.